PENERAPAN MODEL QUANTUM LEARNING UNTUK MENINGKATKAN KREATIVITAS DAN PRESTASI BELAJAR - Ina Herlina (DIADIK, 2022)
Describe the applying quantum learning model to improve students’ creativity and learning achievement at fifth graders in SD Negeri 1 Pagar Alam on science lesson. The problem formulation in this research are 1) Can applying quantum learning improve students’ creativity at fifth graders in SD Negeri 1 Pagar Alam? 2) Can applying quantum learning improve students’ learning achievement on science lesson at fifth graders in SD Negeri 1 Pagar Alam? 3) How effective quantum learning improve students’ learning achievement on science lesson at fifth graders in SD Negeri 1 Pagar Alam? The aims of this study to describe the application of Quantum Learning model to improve students’ creavity and learning achievement in science subject at fifth graders at SD Negeri 1 Pagar Alam. The research design used classroom action research and quasi-experimental. The research subjects were fifth C graders of SD Negeri 1 Pagar Alam year 2021/2022. The quasi-experimental sample is fifth A and fifth B graders of SD Negeri 1 Pagar Alam. The research instrument observation sheets and test. The research data were analyzed by descriptive statistics, mean, percentage, and t-test. The results showed the observation by observer 1 and 2 toward students’ creativity, is obtained the mean score in cycle I is 2,25 with category “less”. In the cycle II is with category “good” and students’ creativity in cycle III is 3,59 with category “excellent”. Creativity improving is followed by increasing the students’ learning achievement from cycle I to cycle III. And the t-test between experimental and control class is obtained t-count > t-tabel (3,163 > 2,000). The results showed the application of quantum learning model can improve students’ creativity and learning achievement at fifth graders in SD Negeri 1 Pagar Alam